2012
DOI: 10.1210/er.2010-0031
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Sex Steroids in Lung Health and Disease

Abstract: Sex differences in the biology of different organ systems and the influence of sex hormones in modulating health and disease are increasingly relevant in clinical and research areas. Although work has focused on sex differences and sex hormones in cardiovascular, musculoskeletal, and neuronal systems, there is now increasing clinical evidence for sex differences in incidence, morbidity, and mortality of lung diseases including allergic diseases (such as asthma), chronic obstructive pulmonary disease, pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
326
3
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(345 citation statements)
references
References 454 publications
5
326
3
11
Order By: Relevance
“…In fact, there is increasing clinical evidence for sex differences in the incidence, morbidity and mortality of lung diseases including allergic diseases (such as asthma), chronic obstructive pulmonary disease, pulmonary fibrosis and lung cancer, as well as pulmonary hypertension. 54,55 A recent study showed that the androgen receptor (AR) is expressed in type II pneumocytes and the bronchial epithelium of murine lung and that androgen treatment increases AR protein levels in lung cells, 56 suggesting an important role for androgens in lung function.…”
Section: Testosterone and Ventilationmentioning
confidence: 99%
“…In fact, there is increasing clinical evidence for sex differences in the incidence, morbidity and mortality of lung diseases including allergic diseases (such as asthma), chronic obstructive pulmonary disease, pulmonary fibrosis and lung cancer, as well as pulmonary hypertension. 54,55 A recent study showed that the androgen receptor (AR) is expressed in type II pneumocytes and the bronchial epithelium of murine lung and that androgen treatment increases AR protein levels in lung cells, 56 suggesting an important role for androgens in lung function.…”
Section: Testosterone and Ventilationmentioning
confidence: 99%
“…It has been reported that sex hormones influence almost every aspect of human physiological functions, activities, and behaviors (12). Sex hormones are thought to have a role in the etiology of some cancers; disturbance in sex hormones is an important feature of cancer pathophysiology (13). However, most studies have been done on sex hormone-sensitive cancers in reproductive organs such as breast, prostate, cervix and ovary.…”
mentioning
confidence: 99%
“…For the purpose of clarity, the endocrine regulation of the lung immune system is not addressed in detail in the present review. Readers are referred to recent reviews that are covering this particular topic (Townsend et al 2012a, Wright 2012, Sood & Shore 2013.…”
Section: Mediators Released By Remote Organs On Asm Contractionmentioning
confidence: 99%
“…The effect of sex hormones on asthma, airway responsiveness, and ASM contractility has received considerable interest (Townsend et al 2012a). The results obtained so far are informative and promising, but not yet permissive to conclusive statements due to reported discrepancies.…”
Section: Gonadsmentioning
confidence: 99%